1971
DOI: 10.1507/endocrj1954.18.395
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effect of Hypothalamic Deafferentation on Progesterone-Induced Ovulating Hormone Release in the Rats

Abstract: SynopsisA study was made to analyze the facilitatory effect of progesterone on ovulating hormone (OH) release in proestrous rats. Neural connections to the medial basal hypothalamus (MBH) or to the preoptic-suprachiasmatic (POA-SC) region of the hypothalamus were transected on the morning of proestrus with a curved knife or with an Lshaped knife. After the recovery from the surgical anesthesia, the rats were injected subcutaneously with progesterone, 1 mg per rat, and anesthetized again with pentobarbital duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1972
1972
1978
1978

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It was further presumed in the rats given acute hypothalamic deafferentation with a small knife that the facilitation by progesterone of OH release may be due to the increase in the responsiveness of the medial basal hypothalamus to the ovulatory stimulus coming from the higher CNS (Kobayashi and Miyake, 1971). Uchida et al (1969bUchida et al ( , 1970Uchida et al ( and 1972 of our laboratory also demonstrated that progesterone given on the morning of proestrus causes a few hr advancement along with a…”
Section: Synopsismentioning
confidence: 77%
“…It was further presumed in the rats given acute hypothalamic deafferentation with a small knife that the facilitation by progesterone of OH release may be due to the increase in the responsiveness of the medial basal hypothalamus to the ovulatory stimulus coming from the higher CNS (Kobayashi and Miyake, 1971). Uchida et al (1969bUchida et al ( , 1970Uchida et al ( and 1972 of our laboratory also demonstrated that progesterone given on the morning of proestrus causes a few hr advancement along with a…”
Section: Synopsismentioning
confidence: 77%
“…suggested that adrenaline-containing fibres are involved in mediating the progesterone-induced LH surge; however, it is likely that this noradrenergic synapse lies along the preoptico-tuberal path (Kalra & McCann, 1973). It is still not clear whether the site of action of progesterone in inducing the LH surge lies within the PO-AHA or outside on neurones which project into it (Kaasjager, Woodbury, van Dieten & van Rees, 1971 ;Kobayashi & Miyake, 1971). …”
mentioning
confidence: 99%